2009
DOI: 10.1029/2008jd011431
|View full text |Cite
|
Sign up to set email alerts
|

Radar reflectivity as a proxy for convective mass transport

Abstract: [1] More observations of vertical mass transport in deep convection are needed to improve dynamical understanding of detrainment processes and for verification of transport models. A methodology for using radar reflectivity as a direct observation of vertical transport of mass from the boundary layer to the upper troposphere and lower stratosphere is investigated, and the ''level of maximum detrainment'' (LMD) is proposed. The case investigated is the 26 January 1999 squall line from the Tropical Rainfall Meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(49 citation statements)
references
References 30 publications
3
46
0
Order By: Relevance
“…The data used in this study comes from the TES Global Survey operating mode in which TES makes nadir observations with a 5.3 × 8.3 km footprint, providing near-global coverage approximately every 16 days. TES ozone and CO profiles are provided on 67 vertical levels from the surface to 0.1 hPa and have been extensively validated against in-situ observations Nassar et al, 2008;Osterman et al, 2008;Richards et al, 2008;Lopez et al, 2008). In order to correctly compare TES and model profiles one must account for the limited vertical resolution and the effects of a priori information inherent in the retrieved TES profiles.…”
Section: Observational Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The data used in this study comes from the TES Global Survey operating mode in which TES makes nadir observations with a 5.3 × 8.3 km footprint, providing near-global coverage approximately every 16 days. TES ozone and CO profiles are provided on 67 vertical levels from the surface to 0.1 hPa and have been extensively validated against in-situ observations Nassar et al, 2008;Osterman et al, 2008;Richards et al, 2008;Lopez et al, 2008). In order to correctly compare TES and model profiles one must account for the limited vertical resolution and the effects of a priori information inherent in the retrieved TES profiles.…”
Section: Observational Datamentioning
confidence: 99%
“…These two model categories are also clearly marked for SA, with outflow heights at 190-200 hPa and 300 hPa respectively. Radar reflectivity data was used by Mullendore et al (2009) to investigate the level of detrainment in a convective storm observed over Brazil during January 1999. For this particular event, the maximum detrainment was found to be at around 11 km, or approximately 220 hPa, which is not greatly different than either of the sets of models.…”
Section: Tropical Concentration Profilesmentioning
confidence: 99%
“…In summary, to understand the potential for deep convective transport in certain storm regimes, we need to understand the relationship between the LNB and the observed level of maximum detrainment (LMD, Mullendore et al, 2009). This relationship was analyzed for tropical convection in a recent study by Takahashi and Luo (2012).…”
Section: Introductionmentioning
confidence: 99%
“…This loss of buoyancy leads to vertical convergence of IWC, which is balanced by horizontal divergence. The convective detrainment layer is therefore linked to a local increase in IWC [Mullendore et al, 2009]. We estimate the rate of change of CloudSat IWC with respect to height ( IWC∕ z) and define the base of the detrainment layer as the peak in positive IWC∕ z and the top of the detrainment layer as the peak in negative IWC∕ z.…”
Section: Datamentioning
confidence: 99%
“…NCCs are identified by their high reflectivities caused by heavy rainfall. Observations of ice water content (IWC) data from CloudSat are used to infer the height of the detrainment layer (HDL) [Mullendore et al, 2009]. CloudSat also provides an estimate of cloud top height (CTH); however, CloudSat is primarily sensitive to larger hydrometeors and cannot detect the relatively small ice particles in cirrus anvils near the top of tropical convective storms.…”
Section: Identification and Description Of Clouds And Aerosol Layersmentioning
confidence: 99%